Penggunaan Model Pembelajaran Inquiri Untuk Meningkatkan Berpikir Kritis Siswa Kelas IV MI Walisongo Pada Mata Pelajaran IPA - Siti Ma’rufah Nur Azizah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study aims to improve students' critical thinking in grade IV MI Walisongo students in science subjects, the research method used is Classroom Action Research (CAR), the design used in this study is the Kemmis and Mc. Taggart model in the form of a cycle sequence. Plans (improvements), actions, and observations are then compiled based on reflection, and this process continues in the same way. The data analysis technique in this study uses quantitative and qualitative data. Quantitative data is in the form of data in the form of student learning scores. While qualitative data is obtained during the learning process. The sample in this study is grade IV MI Walisongo students with a total of 19 students. The use of the inquiry method is able to improve critical thinking and student cooperation because in learning using the inquiry method, because the inquiry model actively involves students in problem solving and knowledge discovery. The results of this study indicate that the use of the inquiry method in science learning can improve critical thinking of grade IV MI Walisongo Belahanrejo students. Based on the results of observations of the implementation in cycle I, the average critical thinking of students was 73%, in cycle II the average critical thinking of students was 86%.